2021
DOI: 10.3389/fonc.2021.622430
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Hallmarks of Group 3 Medulloblastoma by Single-Cell Transcriptomics

Abstract: Medulloblastoma (MB) is a highly heterogeneous and one of the most malignant pediatric brain tumors, comprising four subgroups: Sonic Hedgehog, Wingless, Group 3, and Group 4. Group 3 MB has the worst prognosis of all MBs. However, the molecular and cellular mechanisms driving the maintenance of malignancy are poorly understood. Here, we employed high-throughput single-cell and bulk RNA sequencing to identify novel molecular features of Group 3 MB, and found that a specific cell cluster displayed a highly mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A high level of KIRREL2 expression was also associated with unfavorable survival for all second-generation subgroups from II to VII (not shown). However, we did not find any clinical significance for genes which were previously reported as molecular Grp 3 MB prognosticators [ 2 , 8 , 9 , 18 , 19 , 24 , 27 , 33 ] but were not included in the current DEG set (Online Resource Supplementary Table 2).
Fig.
…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…A high level of KIRREL2 expression was also associated with unfavorable survival for all second-generation subgroups from II to VII (not shown). However, we did not find any clinical significance for genes which were previously reported as molecular Grp 3 MB prognosticators [ 2 , 8 , 9 , 18 , 19 , 24 , 27 , 33 ] but were not included in the current DEG set (Online Resource Supplementary Table 2).
Fig.
…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, a more refined understanding of Grp 3 MB molecular heterogeneity is urgently needed for improved risk stratification, optimization of current treatments, and the development of subgroup-directed therapies. Studies investigating the clinical significance of various molecular features in Grp 3 MB at higher genomic resolution have recently been reported, identifying a wide range of prognostically relevant molecular patterns and subtypes [ 2 , 3 , 8 , 9 , 11 , 15 , 18 21 , 24 , 27 30 ]. Thus, combined multiple class-definition approaches to DNA-methylation profiles of Grp 3/Grp 4 MB identified eight second-generation subgroups, labeled I–VIII [ 21 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous survival analysis study, TUBB4A expression in tumors was found to be associated with MB patients survival, suggesting that TUBB4A may have oncogenic properties ( 72 ). Interestingly, observed PTV is found in the last exon of the gene.…”
Section: Discussionmentioning
confidence: 94%
“…One described mechanism contributing to neoplastic transformation in medulloblastoma is PRC2‐mediated silencing of the gene ADGRB1 coding for the transmembrane protein BAI1 (brain‐specific angiogenesis inhibitor 1) that acts to stabilize the tumor suppressor p53 (Zhang et al., 2020). Interestingly, a study conducted in 2018 revealed opposite implications of EZH2 in a subtype of medulloblastoma (cMyc‐driven Group 3 medulloblastoma) for which a cell type of origin has not been characterized yet (Qin et al., 2021). Here, deletion of EZH2 by gene editing in medulloblastoma cell lines as well as a medulloblastoma mouse model, led to derepression of the oncogenic driver Gfi1 that cooperates with the oncogene Myc and thus mediated both tumor initiation and progression (Vo et al., 2017).…”
Section: Polycomb Regulation In Cancers Of the Cnsmentioning
confidence: 99%